2020
DOI: 10.1111/jocs.14573
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of perioperative blood transfusion practice after coronary artery bypass grafting in the past two decades

Abstract: Background and Aim of the Study Transfusion of blood products after coronary artery bypass grafting (CABG) is associated with increased morbidity and mortality. We evaluated the perioperative use of blood products in patients undergoing CABG in our institution over the past two decades. Methods The study included 18 992 patients who underwent isolated CABG at our hospital between 1998 and 2017. Baseline characteristics of patients and the number of perioperative transfusions during their hospital stay (includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Second, research has shown that females have a higher rate of pRBC transfusions than males due to lower RBC counts, haemoglobin levels and circulating blood volume. As this study includes a wide range of patients, there may be differences in baseline characteristics, such as gender, and multivariate correction will be used in statistical analysis to mitigate potential bias 37–40. Additionally, patients undergoing aortic surgery in our centre tend to have more complex diseases, leading to increased postoperative transfusion requirements compared with other centres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, research has shown that females have a higher rate of pRBC transfusions than males due to lower RBC counts, haemoglobin levels and circulating blood volume. As this study includes a wide range of patients, there may be differences in baseline characteristics, such as gender, and multivariate correction will be used in statistical analysis to mitigate potential bias 37–40. Additionally, patients undergoing aortic surgery in our centre tend to have more complex diseases, leading to increased postoperative transfusion requirements compared with other centres.…”
Section: Discussionmentioning
confidence: 99%
“…As this study includes a wide range of patients, there may be differences in baseline characteristics, such as gender, and multivariate correction will be used in statistical analysis to mitigate potential bias. [37][38][39][40] Additionally, patients undergoing aortic surgery in our centre tend to have more complex diseases, leading to increased postoperative transfusion requirements compared with other centres. Therefore, this study will exclude high-risk populations, including juveniles, adults over the age of 65 years and individuals undergoing thoracoabdominal aorta replacement, to account for heterogeneity.…”
Section: Limitationsmentioning
confidence: 99%
“…Baseline characteristics differed between groups since patients who needed more often packed red blood were older, female and had more comorbidities. Female sex has been shown to act as an independent risk factor for red blood cell transfusion 25 . Obviously, patients received RBC for clinical indications such as anemia and perioperative bleeding and the decision on RBC use was always at the treating anesthesiologist’s discretion.…”
Section: Discussionmentioning
confidence: 99%
“…Increased use of RBC transfusion has been associated with the female sex [11][12][13], as well as with a multitude of other preand perioperative risk factors [14,15]. Despite a decrease in RBC transfusions during recent decades, the female sex has remained an independent predictor of RBC transfusion, as described in a recent study including nearly 19,000 coronary artery bypass grafting (CABG) patients [16].…”
Section: Introductionmentioning
confidence: 99%